Analysis of The Implementation of Crew Responsibilities on Board Ships in Accordance with The Maritime Labour Convention 2006 - Shoffil Tian Mubharoq; Dety Sutralinda; Romanda Annas A; A.A Istri Sri Wahyuni (International Journal of Science and Environment (IJSE), 2026)
This study analyzes the implementation of Crew Member (ABK) responsibilities according to the Maritime Labour Convention (MLC) 2006 on the MV Meratus Kalabahi owned by PT Pelayaran Meratus Line, driven by the gap between regulations and field practices such as work fatigue on domestic Indonesian routes. The aim is to identify compliance with working hours, safety, and crew complaints. Using a descriptive qualitative approach with a population of 20 crew members and a purposive sample of 10-15 respondents, the instruments include interviews, observations, FGDs, and Miles and Huberman analysis (data reduction, presentation, conclusion). The results show good administrative compliance (working hour recording, PPE availability), but field inconsistencies such as double tasks during loading and unloading cause fatigue and low PPE use. The conclusion recommends adjustments to manning levels and safety culture to optimize the MLC 2006.